2006
DOI: 10.1063/1.2354035
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel magnetoresistance in Co nanoparticle/Co–C60 compound hybrid system

Abstract: Co-ITO granular magnetoresistance films fabricated by precipitation of magnetic nanoparticles from amorphous oxide J.A nanometer-scale hybrid film of Co particle/Co-C 60 compound was prepared by alternate deposition of Co and C 60 under UHV condition. All of Raman spectra, magnetization curves, and tunnel conductivity concluded that the hybrid system has a granular structure consisting of Co nanoparticles embedded in a Co-C 60 compound matrix. The magnetoresistance ratio of 26% was obtained at 2 K and 10 kOe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 18 publications
2
56
1
Order By: Relevance
“…The dominated conductivity by the smaller Co nanoparticles might be associated with the nonsaturating MR-H curves at high field. Figure 7 shows examples of the V dependences of the MR(10 kOe) measured at 2 K, 4.2 K and 8 K, 16) respectively. The MR(10 kOe) at 4.2 K shows a decreasing tendency from 24% to the minimum value of 17% with increasing V in the LB region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominated conductivity by the smaller Co nanoparticles might be associated with the nonsaturating MR-H curves at high field. Figure 7 shows examples of the V dependences of the MR(10 kOe) measured at 2 K, 4.2 K and 8 K, 16) respectively. The MR(10 kOe) at 4.2 K shows a decreasing tendency from 24% to the minimum value of 17% with increasing V in the LB region.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15] Very recently, we have shown that the alternately (alt-) deposited C 60 -Co film exhibits the remarkable TMR ranging from 10% to 80%. 16,17) In the present paper, magnetic properties of the altdeposited Co/C 60 -Co film are described, and the structure and the magnetic field/bias voltage dependent magnetotransport behaviors 16,17) are discussed based on them.…”
Section: Introductionmentioning
confidence: 99%
“…3 for P versus V G indicate that the spin injection can be controlled by changing the gate voltage and positive or negative values for the spin polarization may be obtained, depending on the value and the sign of gate potential. The magnitude of P can exceed 90% for certain values of gate voltage which is considerably higher than that calculated for Co-nanowire@CNT (66%) [5] and those measured for Co-cluster/C 60 mixtures (70%) [7], Co-nanoparticle/Co-C 60 compounds (40%) [11] and Co crystals (42%) [48].…”
mentioning
confidence: 87%
“…For example, ab initio calculations showed that Co atoms in CNTs can provide strong spin polarization and considerable magnetic moments [5]. The electrical and magnetic properties of C 60 -Co nanocomposites have also been studied [7,11,12] and tunnel magnetoresistance ratios up to about 30% at low bias voltages were reported, indicating significant spin polarizations [7]. Recent density functional theory (DFT) studies of encapsulated Co atoms in C 60 molecules [18] found hybridization between Co and C 60 orbitals and the most stable structure of Co@C 60 to have the Co atom on top of a hexagonal face.…”
mentioning
confidence: 99%
See 1 more Smart Citation